Radiation-induced accelerated aging of the brain vasculature in young adult survivors of childhood brain tumors - Remes TM; Suo-Palosaari MH; Koskenkorva PKT; Sutela AK; Toiviainen-Salo SM; Arikoski PM; Arola MO; Heikkila VP; Kapanen M; Lahteenmaki PM; Lonnqvist TRI; Niiniviita H; et al. (OXFORD UNIV PRESS, 2022)
Background. Cranial radiotherapy may damage the cerebral vasculature. The aim of this study was to understand the prevalence and risk factors of cerebrovascular disease (CVD) and white matter hyperintensities (WMHs) in childhood brain tumors (CBT) survivors treated with radiotherapy.
Methods. Seventy CBT survivors who received radiotherapy were enrolled in a cross-sectional study at a median 20 years after radiotherapy cessation. The prevalence of and risk factors for CVD were investigated using MRI, MRA, and laboratory testing. Tumors, their treatment, and stroke-related data were retrieved from patients' files.Results. Forty-four individuals (63%) had CVD at a median age of 27 years (range, 16-43 years). The prevalence rates at 20 years for CVD, small-vessel disease, and large-vessel disease were 52%, 38%, and 16%, respectively. Ischemic infarcts were diagnosed in 6 survivors, and cerebral hemorrhage in 2. Lacunar infarcts were present in 7, periventricular or deep WMHs in 34 (49%), and mineralizing microangiopathy in 21 (30%) survivors. Multiple pathologies were detected in 44% of the participants, and most lesions were located in a high-dose radiation area. Higher blood pressure was associated with CVD and a presence of WMHs. Higher cholesterol levels increased the risk of ischemic infarcts and WMHs, and lower levels of high-density lipoprotein and higher waist circumference increased the risk of lacunar infarcts.
Conclusions. Treating CBTs with radiotherapy increases the risk of early CVD and WMHs in young adult survivors. These results suggest an urgent need for investigating CVD prevention in CBT patients.